Impact of Demonetization on E-Commerce in Indian Economy - Kaur, Harmeet (Journal of Commerce and Trade, 2017)
Demonetization has given a boost to digital payments and is encouraging people to shop online more. This will definitely provide an opportunity for e-commerce players to push customers towards adopting cashless instruments and recalibrate business models to incentivize cashless instruments. E-commerce (electronic commerce or EC) is the buying and selling of goods and services, or the transmitting of funds or data, over an electronic network, primarily the internet. These business transactions occur either as business-to-business, business-to-consumer, consumer-to-consumer or consumer-to-business. On November 8th 2016, India came to a standstill when Prime Minister Narendra Modi Ji announced the demonetization of Rs 500 and Rs 1,000 currency notes of the Mahatma Gandhi series. 86 per cent of the currency in circulation ceased to become legal tender after midnight of that day. Demonetization aims at pushing consumers towards making digital payments, thereby contributing to a cashless economy. Niti Aayog published a report on the growth of digital payments in India post-demonetization. Despite bringing chaos in its initial days, demonetization in the long run is considered beneficial to the growth of e-commerce in India. One of the long term benefits for the e-commerce industry is reduction in payments via Cash on delivery (COD). More companies now try to entice consumers directly online, using tools such as digital coupons, social media marketing and targeted advertisements. JEL Classification : A 12, E 41, E 52, L 81.